Loss and tax treatment of income tax for energy losses in Peruvian electricity distributors - Merma Paredes, Herbert Edison (2022)
Objective: Determine the relationship between the losses in power distribution and the tax treatment of income tax for losses of electricity within Peruvian electricity distributors, 1997-2014. Method: The study was approached through the quantitative research method, had a descriptive and correlational level, and the design was non-experimental. It involved a non-probabilistic sample of 22 electric power distribution companies. Results: As a result, a P value = 0,008 and a Rho coefficient = -0,572 were found, which showed that the decrease is significantly related to the tax treatment of energy losses. Conclusion: The lack of distinction of power losses has a significant negative effect on the tax treatment given to income tax in electricity distribution companies in Peru, period 1997-2014; therefore, the greater the ignorance concerning tax treatment of electricity loss, the poorer the tax treatment of electricity losses will be.